A Symbol of Habsburg Military Power: the Slavonian General Command Palace in Osijek (1723) - Horvat-Levaj, Katarina; Podmanicki, Margareta Turkalj (My University, 2020)
The Palace of the Slavonian General Command in Osijek was built in 1723-1724 for the needs of the administration of the Slavonian Military Frontier, formed after the Karlowitz Treaty (1699). In keeping with its preeminent purpose as the seat of the Imperial War Council representatives, the palace stands out with a richly diversified exterior accentuated by a portal with atlantes, and a complex interior organized around a three-aisled vestibule. This gave it an outstanding position in the context of kindred administrative buildings in the wider Central European region, indicating that the origins of the design were in the Baroque architecture of Vienna. The project itself emerged from the circle of military architects engaged in work on the border fortress cities of the Habsburg Monarchy, whose fortification was supervised by Eugene of Savoy, as President of the Imperial War Council.
Keywords: Palace; Slavonian General Command; Osijek; Habsburg Monarchy